PENGGUNAAN KATA SAPAAN DALAM BAHASA MELAYU KUTAI - Wenny Rusbiyantoro (PAROLE: Journal of Linguistics and Education, 2011)
Kutai Malay language is the language that is widely used to communicate in East Kalimantan, especially in the territory of the former Kingdom of Kutai Kartanegara. This study tries to describe the use of address terms in Kutai Malay language and factors that influence the use of it. This research project uses sociolinguistic approaches associated with theories of ethnography of communication developed by Hymes, and is conducted in 3 stages. First, in compiling data, the writer uses the interview technique, listening technique, and questionnaires. Secondly, in data analysis, she uses the method of equivalent translation and pragmatics. Thirdly, in presenting the results of the analysis, she uses informal methods, in which words are written without technical symbols. The results show that Kutai Malay language has a number of address terms. They are kinship address, pronouns, proper names, titles of nobility, zero markers, and epithets.   Keywords  :    terms of address, Kutai Malay language, kinship, social factors